2012
DOI: 10.1177/0165025412467584
|View full text |Cite
|
Sign up to set email alerts
|

Development of face scanning for own- and other-race faces in infancy

Abstract: The present study investigated whether infants visually scan own- and other-race faces differently as well as how these differences in face scanning develop with age. A multi-method approach was used to analyze the eye-tracking data of 6- and 9-month-old Caucasian infants scanning dynamically displayed own- and other-race faces. We found that 6-month-olds showed differential fixation, fixating significantly more on the left eye and mouth of own-race faces, but more on the nose of other-race faces. Infants at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
67
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 25 publications
12
67
6
Order By: Relevance
“…Interestingly, discrimination at 9 months was assessed using a new face set, suggesting that perceptual learning due to exposure transferred to new identities. A recent study further showed that 9 month old infants have a stronger eye-focus when viewing own-race compared to other-race faces, suggesting that enhanced viewing of the eyes may be associated with exposure and experience at a very young age [41]. These questions about the relative contribution of general (perceptual) learning effects in training facial expression categorization could be investigated further by directly comparing the benefits of supervised and unsupervised learning in facial expression and identity recognition training tasks.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, discrimination at 9 months was assessed using a new face set, suggesting that perceptual learning due to exposure transferred to new identities. A recent study further showed that 9 month old infants have a stronger eye-focus when viewing own-race compared to other-race faces, suggesting that enhanced viewing of the eyes may be associated with exposure and experience at a very young age [41]. These questions about the relative contribution of general (perceptual) learning effects in training facial expression categorization could be investigated further by directly comparing the benefits of supervised and unsupervised learning in facial expression and identity recognition training tasks.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, when such fine-grained spatial effects can not be hypothesized in terms of easily distinguishable AOIs, but are of the researcher’s interest, data-driven approaches that statistically compare entire fixation maps may be much better suited (see, e.g., Caldara & Miellet, 2011). Such data-driven approaches have already been adopted for face processing in typical adults (Arizpe, Kravitz, Yovel, & Baker, 2012; Blais, Jack, Scheepers, Fiset, & Caldara, 2008; Caldara, Zhou, & Miellet, 2010), infants (Xiao, Xiao, Quinn, Anzures, & Lee, 2013), and ASD participants (Shi et al, 2015; Yi et al, 2013; Yi et al, 2015). To conclude, the purpose of the research, combined with the stimuli used, should drive the choice of AOI and the analysis type.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been observed among individuals from not only adults (Brielmann, Bülthoff, & Armann, 2014; Fu, Hu, Wang, Quinn, & Lee, 2012; Goldinger, He, & Papesh, 2009; Wu, Laeng, & Magnussen, 2012; Brielmann, Bülthoff, & Armann, 2014), but children (Hu, Wang, Fu, Quinn, & Lee, 2014; Kelly et al, 2011) and even infants (Liu et al, 2011; Wheeler et al, 2011; Xiao, Xiao, Quinn, Anzures, & Lee, 2012). For example, Fu et al (2012) recently demonstrated that the race of a face can influence participants’ scanning patterns such that Chinese participants spend more time looking at the eye region of Caucasian faces relative to Chinese faces, and more time looking at the nose and mouth of Chinese faces relative to Caucasian faces.…”
Section: Introductionmentioning
confidence: 90%